2022
DOI: 10.3389/fped.2021.780830
|View full text |Cite
|
Sign up to set email alerts
|

Robotics-Assisted Pediatric Oncology Surgery—A Preliminary Single-Center Report and a Systematic Review of Published Studies

Abstract: AimThe use of robotics-assisted surgery in oncology has been proved effective and safe in adults. Despite these results, the use of robotics has been rarely reported for pediatric oncology. Our review aims to evaluate the safety and feasibility of robotics-assisted surgery in this field, analyzing our experience and performing a systematic review of the most recent studies.MethodsWe reviewed all patients affected by an oncological disease who underwent a robotics-assisted procedure at our institute. We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Even if robot-assisted surgery in oncology has been demonstrated to be effective in adult population, in pediatric age its use is still limited with few studies conducted on this subject. This could be probably due to the scarce incidence of this disease and to the characteristic of pediatric tumors, which frequently presented a rapid growth, with the need of other non-surgical approach, such as neoadjuvant chemotherapy or radiotherapy ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if robot-assisted surgery in oncology has been demonstrated to be effective in adult population, in pediatric age its use is still limited with few studies conducted on this subject. This could be probably due to the scarce incidence of this disease and to the characteristic of pediatric tumors, which frequently presented a rapid growth, with the need of other non-surgical approach, such as neoadjuvant chemotherapy or radiotherapy ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various oncological procedures for different kind of pediatric tumors were described in literature, such as nephroblastomas, adrenals tumors, pancreatic tumors, germ-cell tumors, thymic tumors, shifting through malignant, borderline or benign tumors. Nephroblastomas and ovarian tumors are most frequently illustrated ( 74 - 77 ). Robot-assisted laparoscopy for abdominal or pelvic tumors, robot-assisted retroperitoneoscopy or robot-assisted thoracoscopy were described.…”
Section: Discussionmentioning
confidence: 99%
“…CPAM: Congenital pulmonary airway malformation tumors out of 134 patients (14). Blanc et al (15) reported their experience with 100 oncologic patients and formulated a guideline for patient selection.…”
Section: Morgagni Herniamentioning
confidence: 99%
“…Vatta et al conducted a retrospective analysis of 14 children who received robot-assisted tumor resection. 56 The tumors involved included mature teratoma, serous papillary cystadenofibromas of the fallopian tube, ovarian cystadenoma, type 3 sacrococcygeal tumor, neuroblastoma and intermixed ganglioneuroblastoma. All tumors were successfully resected without conversion to open surgery, and no recurrence or complications occurred during follow-up.…”
Section: Application Of Ras In Pediatric Surgerymentioning
confidence: 99%